Amino acid composition, mineral contents and protein solubility of some lima bean (Phaseolus lunatus l. Walp) seeds coat. (July 2015) - Seidu, Kudirat Titilope; Osundahunsi, Oluwatooyin Faramade; Olaleye, Mary Tolulope; Oluwalana, Isaac Babatunde
Abstract: Seeds coat of four lima beans ( Phaseolus lunatus ) varieties were subjected to standard analytical techniques in order to evaluate proximate, amino acid, mineral composition and protein solubility. The proximate analysis indicates moisture content in the range of (3.17–4.96%), crude protein (14.53–15.93%), fat (0.62–0.74%), crude fibre (32.59–33.59%), ash (2.43–3.88%), and carbohydrate (47.11–48.62%) on dry weight basis. The most abundant mineral element in the studied seeds coat was potassium 361.20–459.51 mg/100 g followed by sodium 71.27–102.51 mg/100 g and magnesium 83.20–95.23 mg/100 g. Calcium, phosphorus, iron and zinc were also present in significant amount while lead, cobalt and nickel were not detected. The amino acid profile demonstrates nutritionally acceptable results for the samples due to the high levels of essential amino acids in g/100 g protein such as lysine 6.42–7.41, leucine 7.51–8.37, arginine 4.42–7.02 and phenylalanine 5.01–5.49; when compared with FAO/WHO standard; with essential amino acids (TEAA) 49.47–51.07 g/100 g protein. Glutamic and aspartic acid were the most abundant amino acid in all the samples. The protein solubility profiles showed minimum values at pH 4 and more than 70% soluble at pH 10. The study has shown the potentials of lima bean seeds coat, an agro by-products in the development of new functional ingredients for food enrichment to provide an economic alternative raw material for food industries. Highlights: Lima bean seeds coat contains substantial amounts of essential amino acids. High in nutritional mineral elements. Showed high protein solubility with potential application in food system.